Managing Assessment Data and Dual Curriculum Integration in Indonesian Islamic Primary Education: A Case Study from Indonesia - Nurjannah, Nurjannah; Prastowo, Andi (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
This study aims to analyze the implementation of the dual curriculum policy in educational planning, focusing on assessment data management at Al Azhar Elementary School. This study is motivated by the complexity of assessment data management in a dual curriculum system that integrates the National Curriculum and the Cambridge Curriculum. The study used a qualitative approach with a case study method through in-depth interviews with various educational stakeholders, learning observations based on Cambridge International Standards, and dual curriculum documentation studies. Data were analyzed using thematic analysis techniques with a focus on the planning, implementation, and evaluation aspects of assessment data management. The results show that the dual curriculum assessment data management planning has been well integrated through a structured documentation system and a digital platform that facilitates tracking of student progress. Evaluations are conducted periodically with stakeholder involvement to ensure quality and accountability. However, several challenges were identified, such as the complexity of the assessment system, the need for teacher competency development, and harmonization of assessment standards. This study recommends the development of a more integrated assessment data management system, a teacher capacity building program in assessment literacy, and strengthening collaboration with Cambridge International to optimize the implementation of the dual curriculum.